2009
DOI: 10.1111/j.1478-3231.2008.01872.x
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophils involved in fulminant hepatic failure are associated with high interleukin‐6 expression and absence of interleukin‐5 in liver and peripheral blood

Abstract: The increased number of intrahepatic eosinophils, besides the high production of IL-6, may be involved in liver dysfunction. In addition, the low presence of IL-5 in liver and peripheral blood may represent a particular pattern of eosinophil behaviour in human liver failure, which may also involve MIP-1alpha. Further ex vivo studies are necessary to evaluate the specific role of eosinophils in FHF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…Which was similar to the observations of fulminant hepatic failure where eosinophils with high IL-6 expression were reported to be involved in liver damage [41].…”
Section: Discussionsupporting
confidence: 91%
“…Which was similar to the observations of fulminant hepatic failure where eosinophils with high IL-6 expression were reported to be involved in liver damage [41].…”
Section: Discussionsupporting
confidence: 91%
“…The elevated plasma levels of IL-8 that were detected in all cases of ALF are also described in patients with drug-induced ALF and are correlated with granulocyte migration into the liver parenchyma[5,41]. The elevated levels of circulating IL-6 and TNFα, also described by others[42,43], have been related to attempts at liver regeneration[44,45] and liver injury[46], respectively.…”
Section: Discussionmentioning
confidence: 92%
“…C3 is a major component of the complement cascade, present at the early stage of liver inflammation [ 37 ], and C3 can regulate efflux and metabolism of steroid lipids in hepatocyte proliferation [ 18 , 38 ]. In our previous report, plasmatic elevation titers of systemic inflammatory mediators (TNF- α , IL-6, IL-8, IL-10, IFN γ , and total mtDNA) were demonstrated in ALF patients [ 7 , 22 , 23 , 39 ]. Similarly, other authors described the synergic effect of IL-1 beta and IL-6 on C3 mRNA transcription and C3 secretion in rat hepatocytes [ 40 ] since hepatocytes and Kupffer cells constitutively express receptors for C3 and C5a [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 98%
“…Inclusion criteria included the presence of coagulopathy (INR ≥ 1.5) and encephalopathy score above II, according to O'Grady et al [ 21 ] and as described previously [ 7 , 22 , 23 ]. Clinical details of the study population are shown in Table 1 .…”
Section: Methodsmentioning
confidence: 99%